An ethnographic enquiry into the use of sports science and technologies in professional rugby - Baker, C. E. (Durham: Durham University, 2012)
Sports Science and Sports Medicine are becoming an inherent part of the landscape of high performance sports environments. Such is their visibility, that there are currently over 25,000 students training as sports scientists alone; a number greater than the other classical sciences combined. Through an ethnographic study of two professional rugby teams over the course of 12 months, it is shown that the ways in which these technologies and knowledge are deployed in the field differ substantially from their academic and philosophical basis. Drawing upon the work of Foucault, Goffman and Bourdieu, it is suggested that the use of science and technologies within the Medical and Strength and Conditioning departments alters in light of the physical location, the staff involved and the perceived attachment of these tools to higher order knowledge structures derived from beyond the immediate field of enquiry. Moreover, it is argued that the justification for the adoption of `science` in these specific subcultural domains more often relates to social, political and operative means rather than the theoretical bases cited. A typology of use is presented in an effort to clarify the factors affecting the use of Sports Science and Sports Medicine in elite sport, and the implications that these have for the staff, athletes and serving knowledge bases. Notions of identity, surveillance and self governance are central in understanding the relative ease with which technologies of performance have managed to infiltrate the studied environments, and it is posited that similarities may exist in other cultures synonymous with elite sport. This is an ethnography of `science in action`.